Legal Protection of The Rights of Indonesian Citizens for Children in Lifetime Mixed Marriages - Dian Andriani; Dedy Ardian Prasetyo (Ridwan Institute, 2023)
This study focuses on the first problem how to determine the principles of ius sanguinis and ius soli in relation to the status of children from mixed marriages, second, how the concept of legal protection for children from mixed marriages in guaranteeing human rights in the future. The method used in this research is normative juridical research with a research approach in the form of a normative approach. The results of the study show that dual citizenship for life is still difficult to do in Indonesia because Article 6 of the citizenship law adheres to the principle of single citizenship. On the principle of